Erratum: Corrigendum to ″unconstrained optimisation for the design of distillation columns″ (Comp. and Chem. Eng. (1999) vol. 23 (S475-S478) PII S009813549900040X) - Hoch, Patricia Monica (2000)
Corrigendum to unconstrained optimization for the design of distillation columns